Pengaruh Online Distribution Channels (ODS) Terhadap Hotel Revenue - Suci Sandi Wachyuni; Kadek Wiweka; Melyana Liman (Journal of Tourism and Economic, 2018)
The trend of market developments or consumers in utilizing technology as part of their lifestyle, encourages the accommodation industry to make innovations related to technology and the internet. The purpose of this study is to see the relationship between online distribution channels, especially OTAs on hotel performance in terms of income. This study found that OTA was very effective in increasing sales at Dreamtel Hotel Jakarta, where the income originating from OTA for 3 years compared to walk-in guests had a significant difference. However, hotel sales through online travel agents still have problems when using an online booking system, including the delays in connection between the online travel agent system and hotel systems, the difficulty of changing the schedule for booking rooms, and booking based on "availability on availability" must be confirmed to the parties hotel. The limitation of this study is only studying the role of OTA on the income side. Future research is expected to be able to examine other, more complex sides, such as their effects on employee performance, brand image, promotion, and customer satisfaction. This research is expected to provide information related to the important role of OTA for the development of hotel business in the future.